REDOX-RESPONSIVE CROWN ETHERS CONTAINING A CONJUGATED LINK BETWEEN THE FERROCENE MOIETY AND A BENZO CROWN ETHER - Beer, P; Blackburn, C; Mcaleer, J; Sikanyika, H (1990)
The syntheses of new redox-active crown ethers 8a, 8b, 9a, and 9b containing cis- and trans-conjugated olefinic linkages between the ferrocene redox center and respectively benzo-15-crown-5 and N-phenylaza-15-crown-5 are described. The sodium cation forms 1:1 stoichiometric complexes with the trans ferrocenyl ionophores 8b and 9b, whereas potassium produces 1:2 intermolecular sandwich complexes with the same ligands, which were also observed by fast atom bombardment mass spectrometry. Electrochemical investigations reveal the binding of Na+, K+, and Mg2+ guest cations at the respective crown ether coordinating sites results in shifts of the ferrocene oxidation wave to more positive potentials if a conjugated π-electron system links the heteroatoms of the ionophore to the redox center. The magnitude and type (one or two waves) of the anodic shift are related to the charge:radius ratio of the cationic guest, Mg2+ producing the largest value and K+ the smallest. © 1990 American Chemical Society.